Skin mechanobiology and biomechanics: from homeostasis to wound healing - Fernandes, Maria G. (2019)
Human skin represents the largest organ in the body by surface area, acting as a protective barrier from the environment. It constantly counteracts extrinsic and intrinsic mechanical forces during our daily lives. This is because the skin has remarkable biomechanical properties that are uniquely suited to its function. While it is relevant to know how skin tissue deforms and fails, it is even more important to understand how mechanical forces act on skin tissue to maintain tissue physiology and to regulate inherent biological processes such as wound healing. Skin contraction during wound healing is an example of how mechanical stimuli are important to wound closure. However, the scar formed after skin repair is a downside effect of skin mechanical contraction. Awareness of these processes has potentiated the creation of therapies to reduce scarring, but since the underlying mechanobiological mechanisms are not fully understood, there is still space for improvement. This chapter reviews the state of the art of skin biomechanics and mechanobiology at homeostasis and wound healing. The impact of the mechanical properties of the wounds on the rate and quality of wound healing are analyzed. The way this knowledge can improve wound healing and relieve scarring through new therapies is further discussed.